SARUNGISASI BUAH KAKAO KLON MCC01 DAN MCC 02 DI KABUPATEN SOPPENG SULAWESI SELATAN - Lilis Lilis; Rahmiana Rahmiana; Isnaeni Isnaeni; Virna Virna; Nurul Hikma; Syahruni Thamrin (Jurusan Budidaya Tanaman Perkebunan, Politeknik Pertanian Negeri Pangkajene Kepulauan, 2022)
Cocoa production in South Sulawesi decreases from year to year one of the causes due to the attack of cocoa borer pests. The observations aimed to find out the effect of condomizing on MCC 01 and MCC 02, and to see which clones were resistant and more susceptible to PBK pest attacks through condomizing. The method of determining respondents is done deliberately and the determination of samples by determining cocoa tree samples deliberately by choosing a healthy tree and then condomized and without condemned by marking each sample tree. The results showed that condomizing can reduce cocoa fruit affected by PBK, attack rate and intensity of damage is classified as moderate, and MCC 02 is more resistant to PBK pests.